Breaching the Fortress Wall - Jackson, Brian A.; Chalk, Peter; Cragin, Kim; Newsome, Bruce; Parachini, John V. (RAND Corporation, 2023)
Technology systems play a key role within a larger, integrated strategy to target groups' efforts and protect the public from the threat of terrorist violence. This study draws on relevant data from the history of a variety of terrorist conflicts to understand terrorists' counter-technology efforts. Fully exploring adversaries' counter-technology behaviors can help make the best choices to protect from the nation from the threat of terrorism.